Penerapan Sistem Informasi Geografis (GIS) dalam Pemetaan Kerajinan Kain Tenun dan Gerabah untuk Meningkatkan Potensi Kerajinan di Kabupaten Lombok Timur - Aris Sudianto; Muhamad Sadali (Infotek: Jurnal Informatika dan Teknologi, 2018)
East Lombok is one of the existing districts in West Nusa Tenggara Province that is able to produce handicrafts that are in great demand by tourists visiting the island of Lombok. One of the handicrafts produced in East Lombok Regency is Woven and Pottery. Woven fabrics and pottery produced by people in East Lombok regency, no less good than those in other areas. However, because of the development of the era, not many of the younger generation who want to continue and maintain the sustainability of this Weaving and Pottery. The time and effort required to make this type of craft is not small, where to manufacture 1 woven fabric alone can spend up to 1 week, and also for making 1 pottery can take days with long process. It is also what makes the price of woven cloth and pottery become more expensive compared with other types of crafts. Another problem that occurs is the marketing of handicrafts of woven fabrics and pottery is still difficult to do, given the location of the craftsman is still somewhat distant from the hustle of the city but also the limitations of the surrounding community about the utilization of information technology is still very lacking, so the craftsmen choose to market their products elsewhere . To overcome these problems, in this case to help introduce and market the woven and earthenware, needed a system that can know the details of location and information quickly and accurately, which in this research utilizing Geographic Information System (GIS) technology that can analyze and monitor the location quickly. Application of Geographic Information System Technology (GIS) aims to overcome the problems faced by pegerajin especially in terms of marketing and also to further introduce and preserve the craft of Weaving and Pottery so that it can increase the potential of handicrafts in East Lombok regency.DOI : 10.29408/jit.v1i2.882